Digital Trade Network Status and Its Impact on Export Complexity - Li, Jingying (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of information and communication technology, digital trade has become a key driving force for promoting economic growth, promoting enterprise transformation and improving the position of the global value chain. This paper selects the OECD service trade database digital trade agency data collection, using social network analysis, build the digital trade network between 22 countries in 2010-2021, and analyzes the development and evolution of digital trade network and the status of a country or a region in the digital trade network, the research results show that: observe the increasing digital trade between sample countries (regions), the number of economies trading partners, the breadth of digital trade between sample countries. From the perspective of the individual network characteristics of the economies, the fluctuation of the top countries or regions is small, while the fluctuation of the latter countries is large, indicating that the pattern of digital trade network has not been finalized, and there is still room for development. In addition, this paper also based on the panel data model empirical analysis of a country or regional digital trade network status on the influence of the export technology complexity, the study found that near the center of a countrys export technology complexity presents significant positive effect, shows that in the digital trade network, a countrys trade accessibility is higher, will have a positive impact on its export technology complexity.